Use of Augmented Reality (AR) in Mobile Learning for Natural Science Lessons - Erwis, Fauzi; Jixiong, Cai; Rahayu, Novi; Raharja, Agung Rachmat; Zebua, Rony Sandra Yofa (Journal of Social Science Utilizing Technology, 2024)
Background. The development of information technology continues to change from time to time, especially Augmented Reality (AR), which has opened up new opportunities in education by introducing more interactive and interesting learning concepts. In the context of Natural Science (Science) lessons, the use of Augmented Reality in Mobile Learning offers the potential to increase students’ understanding of complex concepts through visual and practical-based learning experiences. Purpose. This research aims to determine the use of Augmented Reality in Mobile Learning for learning Natural Sciences. The focus is to assess the impact of using Augmented Reality on understanding Natural Science concepts, learning motivation, and student engagement. Method. The research method used in this research is a quantitative method using a random control experiment where two groups of students are divided randomly, one group uses conventional learning methods while the other group uses the Mobile Learning application with Augmented Reality features. Data was collected through a learning motivation questionnaire. Results. The research results showed that the group that used Augmented Reality in Mobile Learning showed an increase in understanding of Natural Science concepts compared to the control group that used conventional methods. In addition, they also show higher levels of learning motivation and more active involvement in the learning process.   Conclusion. The conclusion of this research is that the use of Augmented Reality in Mobile Learning for learning Natural Sciences has the potential to increase learning effectiveness by providing a more interactive, visual and practical learning experience. The results of this research show that Augmented Reality can be a valuable tool in increasing students’ understanding of Natural Science concepts, as well as motivating them to learn better. Therefore, the integration of Augmented Reality in Mobile Learning can be an effective strategy in improving the quality of Natural Sciences education in this digital era.